Experimentally simulating adiabatic behaviour: capturing the high strain rate compressive response of polymers using low strain rate experiments with programmed temperature profiles - Trivedi, AR; Song, P; Siviour, CR (Elsevier, 2022)
Polymers are widely used in applications where they may be subjected to impact loading leading to high strain rate deformation. Plastic work on deformation generates heat in the material. At high strain rates, there is insufficient time for this heat to diffuse out of the material, leading to adiabatic conditions. This leads to post-yield thermal softening in the mechanical response, which modifies the material response and must be considered in Engineering design. In this paper, a novel technique is presented in which this adiabatic self-heating can be simulated experimentally at low strain rates using programmed temperature profiles. We show that, in some cases, these simulations can very accurately capture the mechanical response at higher rates, but in others, the replication is less accurate. This may give further insights into the thermodynamics of high strain rate polymer mechanics. This technique therefore enables a number of avenues of research: the work to heat conversion can be investigated systematically; diagnostic tools that are limited to low strain rates can be applied; and we can better understand material behaviour and thereby improve predictive models.